Intelligent Image and Video Interpretation : Algorithms and Applications. - Tian, Jing (Information Science Reference, 2013)
"This book covers all aspects of image and video analysis from low-level early visions to high-level recognition, highlighting how these techniques have become applicable and will prove to be a valuable tool for researchers, professionals, and graduate students working or studying the fields of imaging and video processing"--Provided by publisher.